Effect of Supplementation of Dried Bovine Spleen in the Diet of Broiler Chicken - Shibu KV (Department of Poultry Science, College of Veterinary and Animal Sciences, 1999)
An experiment was conducted to study the effects of dried bovine spleen at different level supplementation viz., 0.1, 0.15 and 0.2 per cent in standard starter and finisher rations on production performance and the economics of broiler chicken, using one hundred and ninety two commercial day-old broiler chicks for a period of eight weeks. The birds were divided into four dietary treatment groups viz., standard broiler ration (T 1), standard broiler ration with 0.1 per cent dried bovine spleen (T 2), standard broiler ration with 0.15 per cent dried bovine spleen (T}) and standard broiler ration with 0.2 per cent dried bovine spleen (T4)' Standard broiler ration was formulated as per BIS (1992) specification for broiler chicken feed. The observations monitored throughout the experimental period were body weight gain, feed intake, feed efficiency, protein efficiency and livability. At the end of the experiment the blood parameters, dressed yield, ready-to-cook yield and organ weights of gizzard, heart, liver and spleen were also determined. The results showed that 0.1 per cent dried bovine spleen supplemented groups attained a higher body weight and 0.15 and 0.2 per cent dried bovine spleen supplemented groups attained a lower body weight than control but not significantly so. The feed intake was significantly higher for the standard diet fed group from fifth week onwards. A positive response was observed in feed efficiency by bovine spleen supplementation which was statistically significant. Upto six weeks the feed efficiency was best for the group fed diet supplemented with 0.1 per cent dried